Demonstrating deep biosphere activity in the geological record of lake sediments, on Earth and Mars. Issue 4 (2nd October 2017) - Parnell, John; McMahon, Sean; Boyce, Adrian
Abstract: The investigation of Gale Crater has highlighted the occurrence of lake sediments in the geological record of Mars. Lacustrine basins include a diversity of potential habitats for life. An analogue terrestrial lacustrine basin of Devonian age in Scotland contains sulphide minerals in several settings where subsurface microbial colonization can be envisaged. Sulphur isotope compositions for the sulphides imply that they were precipitated by microbial sulphate reduction. The data suggest that the search for life in martian lacustrine basins should include investigation of potential subsurface habitats, and that any sulphides in martian lacustrine basins could be useful indicators in the search for life.